Development of an Age-Specific Educational Application to Enhance Public Knowledge of Common Non-Communicable Diseases - Azizah, Nurul (Genius Journal, 2025)
Introduction: Indonesia has experienced a significant increase in non-communicable diseases (NCDs), including diabetes, hypertension, and cardiovascular disorders, affecting individuals across various age groups. These conditions often progress silently and require long-term management. Enhancing public knowledge and awareness is essential for early detection and effective prevention. Objective: This study aimed to develop an interactive educational application tailored to different age groups to improve public understanding and awareness of common NCDs, focusing on their signs, symptoms, and preventive strategies. Methods: A Research and Development (R&D) method was applied using the 4D model, consisting of four phases: Define, Design, Develop, and Disseminate. The development process included a needs analysis, application content and interface design, software development, and dissemination planning. Input from health professionals and target users was integrated to ensure the application’s content accuracy and usability. Results: The final application features a secure login system and age-specific interactive menus that display relevant NCD information, including warning signs, symptoms, and prevention tips. Black-box testing confirmed its functional reliability, while usability testing indicated high user satisfaction. The application positively influenced users' health knowledge, particularly in identifying early symptoms and understanding preventive measures for NCDs. Conclusion: Age-specific digital education tools are effective in increasing public knowledge about NCDs and fostering preventive health behaviors. Integrating such applications into community health initiatives can enhance health literacy and support early intervention strategies across diverse age demographics.